Advanced air electrodes for solid oxide electrolyzer cells - Pan, Zehua (2017)
Solid oxide electrolyzer cells (SOECs), which serve as a highly efficient and viable technology for energy conversion and storage, have drawn great attention in the recent years, especially with the continuous rise of renewable energy usage. However, the high degradation rate hinders the commercialization of this technology. One of the sources of degradation is the air electrodes. Therefore, it is urgent to understand the degradation mechanism of air electrodes and then to develop methods to improve the stability of SOECs. At present, LSCF (La1-xSrxCoyFe1-yO3-δ)-based air electrodes are under intensive research and selected as the air electrode used in this thesis, as the traditional LSM (Sr-doped Lanthanum Manganese Oxide)-based air electrodes usually suffer severely from poor electrochemical activity and tendency to delaminate from YSZ (Yttria Stabilized Zirconia) electrolytes. This thesis gives an in-depth investigation on the degradation mechanism during fabrication and operation of LSCF electrodes in SOECs, and possible solutions to suppress the degradation. Firstly, possible interfacial reactions between LSCF and YSZ during the fabrication stage were investigated. It was found that SrZrO3 second phase can be generated, along with the precipitation of (CoFe)3O4 spinel phase, by sintering YSZ and LSCF powder mixture for 2 h at a sintering temperature of 850 °C or higher. This SrZrO3 second phase can cause substantial increase of the polarization resistance, RP, of the LSCF electrodes on YSZ electrolytes obtained under open circuit voltage (OCV), from 0.03 Ω cm2 to 2.72 Ω cm2 with the increase of the sintering temperature from 800 °C to 1000 °C. By scanning electron microscope (SEM), a thin but dense layer of SrZrO3 was observed covering the whole surface of YSZ electrolyte when LSCF was sintered at 1000 °C, most likely to be a result of the high diffusivity of Sr. Furthermore, it was found that the SrZrO3 second phase caused more severe performance drop in fuel cell mode than in electrolyzer mode. Secondly, the degradation mechanism of LSCF air electrodes during high-temperature anneal under OCV was investigated. It was found that the increase of RP of LSCF under OCV condition showed a linear dependence on the square root of time, indicating diffusion processes. A comparison between the behaviour of the sample before and after nitric acid etching treatment, which can remove the possible surface precipitated substances, showed that the performance has been improved and the degradation rate has been reduced after nitric acid etching treatment. Given that, the degradation is most likely due to the emergence of surface inhibited species on the LSCF electrode, which can be removed by nitric acid treatment. XPS examination showed that the “surface” Sr increased upon the annealing time and decreased upon the nitric acid etching treatment. Consequently, it can be concluded that the degradation of LSCF electrodes under OCV is caused by the surface segregation of Sr-based species. This confirms the detrimental role of surface segregated Sr-based phase on the electrochemical performance of LSCF electrodes. After that, LSCF electrodes on YSZ electrolytes were applied with electrolysis current. During the test at 800 °C, it was found that the applied electrolysis current could suppress the degradation or even activate the electrode. For instance, the RP of the LSCF electrode sintered on the YSZ electrolyte at 1000 °C decreased from 1.53 to 0.59 Ω cm2 after the application of electrolysis current of 1 A cm–2 for 24 h at 800 °C. However, after electrolysis test for 24 h, the LSCF electrode was found delaminated from the YSZ electrolyte. Subsequently, the activation and delamination behaviour was thoroughly studied. As revealed by SEM images, the SrZrO3 layer developed during fabrication stage was found to delaminate from the YSZ electrolyte rather than that the LSCF electrode delaminated from the SrZrO3 layer. Moreover, Co diffusion into the SrZrO3 layer was detected by energy dispersive x-ray and later proven to be able to improve the catalytic activity of the SrZrO3 layer. Then, the catalytic activity of the SrZrO3 layer could render the generation of oxygen at the SrZrO3–YSZ interface. However, owing to the low porosity of the SrZrO3 layer, the generated oxygen cannot diffuse out effectively and accumulated at the interface. Eventually, the bonding was weakened and the delamination of the SrZrO3 layer took place. This finding indicates that to improve the durability of LSCF electrodes, it is critical to prevent the formation of SrZrO3 second phase and Co diffusion during the fabrication and operation of SOECs. At last, a half-cell with a dense GDC interlayer, which can prevent the formation of SrZrO3, was tested for 264 h under 1 A cm–2 electrolysis current at 800 °C. No delamination of the LSCF electrode was found after the test. By comparison, another half-cell with a porous GDC interlayer, which cannot fully prevent the formation of SrZrO3 second phase, was also fabricated and tested under the same condition. Detachment was again found at the interface between the SrZrO3 phase and the YSZ electrolyte. This result validates the above proposed mechanism and proves the effectiveness of the dense GDC interlayer in preventing the delamination problem. The half-cell with dense GDC interlayer will be used for future study.